2019
DOI: 10.1002/cjce.23486
|View full text |Cite
|
Sign up to set email alerts
|

Shear rheological properties of composite fluids and stability of particle suspensions: Potential implications for fracturing and environmental fluids

Abstract: Composite fluids are comprised of particles and polymers and are used for fracking and the in‐situ treatment of subsurface contaminants. This study investigates the correlation between the shear viscoelasticity of guar aqueous solutions and their effectiveness in suspending sand, which is a common fracking proppant. In the absence of a crosslinker, the shear viscous modulus (G”) of 5 g/L guar solutions was greater than the shear elastic modulus (G’). When the crosslinker borax was added, the guar solutions beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…[25][26][27] Polymeric fluids can be used to transport reactive particles in the subsurface, such as nanoscale zero-valent iron particles. 17 These findings are in agreement with other studies, which showed that when the loss tangent δ (δ = G 00 /G 0 ) is high, fluids behave like liquids and settling is promoted, whereas when δ is low, fluids behave like gels and settling is impeded. 17 These findings are in agreement with other studies, which showed that when the loss tangent δ (δ = G 00 /G 0 ) is high, fluids behave like liquids and settling is promoted, whereas when δ is low, fluids behave like gels and settling is impeded.…”
Section: Effect Of Shear Rheology On the Velocity Of Polymeric Fluidssupporting
confidence: 93%
See 4 more Smart Citations
“…[25][26][27] Polymeric fluids can be used to transport reactive particles in the subsurface, such as nanoscale zero-valent iron particles. 17 These findings are in agreement with other studies, which showed that when the loss tangent δ (δ = G 00 /G 0 ) is high, fluids behave like liquids and settling is promoted, whereas when δ is low, fluids behave like gels and settling is impeded. 17 These findings are in agreement with other studies, which showed that when the loss tangent δ (δ = G 00 /G 0 ) is high, fluids behave like liquids and settling is promoted, whereas when δ is low, fluids behave like gels and settling is impeded.…”
Section: Effect Of Shear Rheology On the Velocity Of Polymeric Fluidssupporting
confidence: 93%
“…[1][2][3][4] Previous research showed that colloidal particle settling is markedly different in fluids with identical shear viscous moduli but different shear elastic moduli, with high shear elastic moduli leading to negligible particle settling. 17 These findings are in agreement with other studies, which showed that when the loss tangent δ (δ = G 00 /G 0 ) is high, fluids behave like liquids and settling is promoted, whereas when δ is low, fluids behave like gels and settling is impeded. 28 Therefore, high shear elasticity is desirable to ensure that particles remain suspended in aqueous solution.…”
Section: Effect Of Shear Rheology On the Velocity Of Polymeric Fluidssupporting
confidence: 93%
See 3 more Smart Citations